Effects of muscle morphological characteristics on long-distance running performance - Yoshioka, T.; Nakagaki, K.; Mukai, N.; Nabekura, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2009)
The aim of this study was to determine the relationship between muscle morphological characteristics and running performance. Eighteen elite Japanese male distance runners (10000 m, seasonal best time 29:39.74 0:32.54) completed five 4-min submaximal and approximately 10-min maximal progressive treadmill tests to determine running economy (VO2 at submaximal velocity) and maximal oxygen uptake (VO2max). Axial images of the trunk, thigh and shank muscles were taken by magnetic resonance imaging (MRI). From these images, crosssectional areas (CSAs) of the psoas major, quadriceps femoris, rectus femoris, vastus muscle, hamstring, sartoris, adductor magnus, adductor longus, gracilis, triceps surae, soleus and gastrocnemius were measured. The CSAs were divided by lean-body-mass0.67 measured by air-displacement plethysmography. The mean running economy (VÿO2 at 310 m/min) was 70.9 ml/kgLBM/min and VO2max was 82.0 4.3 ml/kgLBM/min (76.1 3.2 ml/kgBM/min). Simple correlation analysis revealed a negative association between hamstring CSA and 10000 m time (r 0.681, p 0.05). On the other hand, quadriceps femoris CSA was positively associated with 10000 m time (r 0.637, p 0.05). Furthermore, triceps surae CSA was significantly correlated with running economy (r 0.573, p 0.05). Thus, these results suggest that hamstring CSA can explain long distance as well as sprint performance.